Faktor-faktor yang mempengaruhi kualitas hidup pasien kanker tiroid berdiferensiasi baik (DTC) paska tiroidektomi total di Rumah Sakit Umum Pusat (RSUP) Sanglah, Denpasar - I Gusti Ngurah Gde Dwi Aryanata; I Wayan Sudarsa; Putu Anda Tusta Adiputra (DiscoverSys Inc., 2019)
Background: Thyroid Cancer is the most common endocrine cancer. The majority of thyroid cancer (80-85%)Â is well differentiated. Surgery is the treatment of choice for Well-Differentiated Thyroid Cancer (DTC). This research aims to evaluate the quality of life of patients with thyroid cancer who have undergone total thyroidectomy compared to the general population and also assess the influencing factors.Methods: This research includes 50 patients suffering from DTC after total thyroidectomy and 50 participants were selected to represent the general population who are then asked to fill out a detailed questionnaire EORTC QLQ 30 Indonesia Version including demographic data and clinical data as the TSH levels, the type of histopathology and interval of time since diagnosis, taken from the patient's medical record. Data were analyzed using independent t-test and linear regression in STATA 14 for windows.Results: It is evident that the quality of life of patients with DTC after total thyroidectomy is significantly lower compared to the general population (P<0.05). In addition, several factors such as age, educational level and income of the family give a strong influence as for gender, marital status, employment status, and the time interval since diagnosis gives a mild influence to the quality of life (P<0.05). However, TSH levels and type of histopathology was not proven to affect the quality of life (P>0.05)Conclusion: There are several factors related to quality of life among patients with DTC such as age, educational level and income of the family, gender, marital status, employment status, and the time interval since diagnosis